2013
DOI: 10.1128/aac.00269-13
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Antivirulence Agents against Methicillin-Resistant Staphylococcus aureus

Abstract: bAntivirulence agents inhibit the production of disease-causing virulence factors but are neither bacteriostatic nor bactericidal. Antivirulence agents against methicillin-resistant Staphylococcus aureus (MRSA) strain USA300, the most widespread community-associated MRSA strain in the United States, were discovered by virtual screening against the response regulator AgrA, which acts as a transcription factor for the expression of several of the most prominent S. aureus toxins and virulence factors involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 30 publications
(35 reference statements)
1
96
0
1
Order By: Relevance
“…16 The data show that half of patients with pneumonia and sepsis were infected with MRSA. 17 Pneumonia and sepsis are life-threatening diseases with high mortality rates (60% and 63.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…16 The data show that half of patients with pneumonia and sepsis were infected with MRSA. 17 Pneumonia and sepsis are life-threatening diseases with high mortality rates (60% and 63.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In an in silico screen, diflunisal was predicted to inhibit AgrC-mediated phosphorylation of AgrA. Consistent with this prediction, diflunisal treatment inhibited rabbit red blood cell lysis and significantly lowered transcript levels of hla, RNAIII, and psm␣ without affecting bacterial growth (7,11). However, the efficacy of diflunisal in mitigating staphylococcal virulence in vivo has yet to be determined.…”
mentioning
confidence: 86%
“…In silico analyses identified the NSAID diflunisal as a potent inhibitor of AgrA-mediated gene expression (11). We previously demonstrated that Agr-dependent virulence factor production, and in particular synthesis of alpha-type PSMs, significantly contributes to skeletal cell death and bone destruction associated with S. aureus osteomyelitis (5,14,18).…”
Section: Diflunisal Inhibits S Aureus Cytotoxicity Toward Human and mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we have identified small-molecule biaryl hydroxyketone compounds that target the response regulator AgrA and inhibit its interaction with promoter P3, curtailing the production of toxins and virulence factors (8). In a follow-up study, a combinatorial library of 148 compounds was synthesized based on the most efficacious hit compound (9).…”
mentioning
confidence: 99%